FHITlow/pHER2high signature in non‐small cell lung cancer is predictive of anti‐HER2 molecule efficacy. Issue 2 (13th May 2020) - Da Silva, Jordan; Jouida, Amina; Ancel, Julien; Dalstein, Véronique; Routhier, Julie; Delepine, Gonzague; Cutrona, Jérôme; Jonquet, Antoine; Dewolf, Maxime; Birembaut, Philippe; Deslée, Gaëtan; Polette, Myriam; et al.
Abstract: Despite its efficacy in solid tumours, in particular HER2 + breast cancer, HER2‐targeted therapy has given rise to disappointing results in non‐small cell lung cancer (NSCLC). With the aim of refining the target population for anti‐HER2 therapies in NSCLC, we investigated the relationships between HER2 and the tumour suppressor fragile histidine triad (FHIT) in lung tumour cells. First, we observed a negative correlation between FHIT expression and the activated form of HER2 (pHER2) in NSCLC samples and in lung tumour cell lines. Moreover, the silencing or overexpression of FHIT in lung cell lines led to an increase or decrease of HER2 activity, respectively. We also demonstrated that two anti‐HER2 drugs, irbinitinib and trastuzumab, restore a more epithelial phenotype and counteract cell invasiveness and growth of FHIT‐silenced tumour cell lines. Finally, we showed that the FHIT low /pHER2 high phenotype predicts sensitivity to an anti‐HER2 therapy in primary tumour cells from NSCLC patients. Our results show that FHIT regulates the activity of HER2 in lung tumour cells and that FHIT‐inactivated tumour cells are sensitive to HER2 inhibitors. A new subclass of patients with NSCLC may be eligible for an anti‐HER2 therapy. © 2020 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.